The hidden transcripts of sacred song in a South African coloured community - Jorritsma, Marie (International Library of African Music, 2008)
One of my earliest memories of coloured farm workers is the sound of their hymn singing at Sunday morning church services. In my mind, these sounds became intimately connected with my visits to the Karoo, the name for the semi-desert landscape that surrounds the farming town of Graaff-Reinet. These childhood associations resurfaced when, early one Sunday morning in August 2004, I travelled into Kroonvale (the residential area for coloured people on the edge of Graaff-Reinet) to attend the morning service of the Uniting Reformed Church. Brown-red dust, typical of the Karoo, hung in the air as I drove. When I stepped over the church threshold, it seemed as if I collided with a powerful wall of sound. While the congregation sang "Juig Aarde Juig" ("Rejoice Earth Rejoice") at full volume, I reflected on the anomaly of the utter silence about this music in the Graaff-Reinet Museum archive where I had spent the last month searching for historical evidence.
Keywords: South Africa; African Music